(untitled) (Eurasian Journal of Philology Science and Education, 2015)
This article is focused on the bard’s poetry called “Zhyrau”, as a unique oral folklore of Kazakh people, and the source of the historical memory of the past. According to the author, Zhyrau is a rich heritage of the Middle Ages, which brings the spiritual and moral values of the individual and society. Akyns and zhyrau were of great importance, their role as conductor of knowledge about the world, passing them down from generation to generation. Akyns and the zhyrau had a notable impact on the social life of the Kazakhs, affecting students of artistic expression. In his works zhyrau affect important and relevant social issues, spoke on matters of morality, played a significant role in the cultural history of the Kazakh people. Article phenomenon zhyrau considered as a major source of preservation of historical memory of the Kazakh people.